Comparing cytotoxicity of propoxur and Nepeta crispa (Lamiales: Lamiaceae) essential oil against invertebrate (Sf9) and vertebrate (L929) cell lines - Amirhossein Zahirnia; Mitra Boroomand; Hassan Nasirian; Aref Salehzadeh; Sara Soleimani-Asl (Veterinary World, 2019)
Background and Aim: Attempts to use the plant products are to be an appropriate option due to substantial concerns about human health and environmental problems of using synthetic pesticides. Therefore, the cytotoxicity of Nepeta crispa essential oil was compared with propoxur against invertebrate (Sf9) and vertebrate (L929) cell lines.